(untitled) (GENDER EQUALITY: International Journal of Child and Gender Studies, 2020)
Early childhood education is usually better known as education that emphasizes playing while learning, by playing the child has been learning. One of the learning models in PAUD is the center and circle model which is a teaching approach that places children in a proportional position. The concept of early childhood education takes the form of play because play is a child’s world. The point is playing is learning, and learning is playing. The implementation of learning in PAUD with the BCCT approach model is learning that focuses on activities in centers to optimize the multiple intelligences that must be developed in children. In the BCCT approach there are seven learning centers, namely preparatory centers, beam centers, major role playing centers, small role playing centers, natural material centers, art centers and imtaq centers. Progressivism is education that emphasizes the ability of children to be able to deal with social life in a community environment, is also a flow of educational philosophy that supports changes in the implementation of education. Existentialism is a philosophical school that prioritizes human freedom to actualize itself. This view of existentialism is that education is an attempt to liberate humanity from the things that bind it up so that the realization of human existence towards a more humane and civilized. Education aims to shape people into people who are moral, intelligent and can be responsible. Through education, children are expected to have a good attitude, extensive knowledge, and optimal skills.